Appropriate size for transportation to sea cages for juvenile Pacific bluefin tuna Thunnus orientalis (Temminck and Schlegel). (21st November 2020) - Okada, Tokihiko; Honryo, Tomoki; Kawahara, Masato; Takahashi, Ichita; Murayama, Kou; Ishibashi, Yasunori
Abstract: High levels of mortality occur in the fingerling production of juvenile Pacific bluefin tuna (PBF, Thunnus orientalis ), especially just after transportation from land‐based tanks to sea cages. The survival rate drastically declines within 3 days after transportation. To improve aquaculture efficiency, this problem needs to be resolved. We focused on the body size of juvenile PBF. We conducted two experiments using large‐size (Experiment 1; mean body weight, 11.6 g) and small‐size (Experiment 2; mean body weight, 0.5 g) fish to investigate the appropriate size for transportation. Experiment 1, using large‐size juvenile PBF, showed worse outcomes than the control‐1, including increased mortality induced by collisions due to a prolonged period in a land‐based tank and mortality due to the transportation process. In contrast, Experiment 2, using small‐size juvenile PBF, demonstrated high survival without high rates of mortality, even just after transportation. In addition, there were no differences in growth between the treatments at the end of the experiment. Thus, this study suggests that transportation of smaller PBF juveniles than recommended in past studies could improve aquaculture efficiency because of a higher survival rate and shortened duration of hatchery management.